Recurrent secondary hyperparathyroidism after parathyroidectomy due to anterior mediastinum ectopic parathyroid glands in a peritoneal dialysis patient—a case report and literature review - Cao, Wen; Qing, Wei; Ren, Haoyuan; Song, Bin (Frontiers in Medicine, 2025)
BackgroundSecondary hyperparathyroidism (SHPT) is a common complication of end-stage kidney disease (ESKD). Parathyroidectomy (PTX) is a reasonable option for patients with ESRD complicated by refractory SHPT, although only a few cases of ectopic parathyroid glands have been reported in patients undergoing peritoneal dialysis (PD).Case presentationWe present a case of recurrent SHPT after parathyroidectomy due to ectopic parathyroid glands in a patient undergoing long-term PD for approximately 10 years. The ectopic parathyroid glands were identified when performing the first operation, but it was too risky to be removed, and it induced recurrent SHPT. The reoperation was successful, aided by precise localization through Technetium-99m methoxyisobutylisonitrile single photon emission computed tomography/computed tomography (99mTc-MIBI SPECT/CT) imaging and advanced thoracoscopic surgical techniques. The patient received a calcium concentration of 1.75 mmol/L dialysate, combined with adequate calcium and active vitamin D supplementation, immediately after the second PTX, which resulted in the remission of hungry bone syndrome (HBS) within a short time.ConclusionAccurate evaluation of the position and function of the parathyroid gland before PTX is the key to reducing the rates of missed diagnosis and SHPT recurrence. Integrated management based on mineral metabolism assessment is crucial for preventing and treating hungry bone syndrome after ectopic PTX in clinical practice.